Occurrence of Psychiatric Disorders, Self-Sufficiency Problems and Adverse Childhood Experiences in a Population Suspected of Violent Extremism - Grimbergen, Christel; Fassaert, Thijs (Frontiers in Psychiatry, 2022)
Background: Public health-inspired programs for Countering Violent Extremism (CVE) have developed across Europe and the US in a relatively short period of time. Research into these programs is scarce. There is a need for information that helps drive public health interventions. Objectives: to present data on the occurrence of psychiatric disorders, self-sufficiency problems and adverse childhood experiences (ACE) in a population suspected of violent extremism. Method: a cross-sectional study, with data from screening reports for 34 adult subjects included in a multi-agency case-based approach on violent extremism in Amsterdam, the Netherlands. Subjects were screened in the period between January 2016 to date. Screening reports, which included the Screener for Intelligence and Learning Disabilities (SCIL) and the Dutch version of the Self-sufficiency Matrix (SSM-D), were used to gather information on the main outcome measures. Results: Major psychiatric disease categories were mood and anxiety disorders (40.0%), mild intellectual disability (46.7%), personality disorders (43.3%) and psychotic disorders (23.3%). Severe self-sufficiency problems were found in 30.0% of the sample. The most prevalent ACE were emotional neglect (47.1%), household mental illness (44.1%) and loss of a parent (38.2%), 35.3% had been exposed to 4+ ACE. An association was found between NACE and self-sufficiency problems on two domains, namely ‘Mental Health’ (rho = 0.51, p=0.002) and ‘Law and order’ (rho = 0.42, p=0.013). Conclusions: An accumulation of social and psychiatric problems in people suspected of violent extremism underlines the importance of professionals in health and social care being actively involved in developing CVE approaches.